PENGARUH DISKON HARGA, BRAND IMAGE DAN PROMOSI TERHADAP MINAT BELI PADA TOKO DINDASAYUDHA THRIFT DI SITUBONDO DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Kiptiyah, Zainatul; Fandiyanto, Randika; Syahputra, Hendra (Fakultas Ekonomi dan Bisnis, 2025)
This study aims to examine the influence of price discounts, brand image, and promotion on consumer purchase intention at Dindasayudha Thrift Store in Situbondo, with customer satisfaction serving as an intervening variable. The background of this research is grounded in the growing trend of thrifting and the increasing importance of marketing strategies in sustaining and enhancing business competitiveness, particularly among younger consumers. The study employs a quantitative method with a descriptive approach. The sample consists of 98 respondents who are customers of Dindasayudha Thrift Store. Data were collected using a questionnaire and analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS 3.0 software. The findings reveal that price discounts, brand image, and promotion have a significant impact on customer satisfaction, while brand image and promotion also have a direct influence on purchase intention. Furthermore, customer satisfaction has been proven to act as an intervening variable that strengthens the effect of the independent variables on purchase intention. These findings have practical implications for business practitioners, enabling them to optimize their marketing strategies and enhance customer satisfaction, ultimately leading to increased purchase intention.